How History is Made A Student’s Guide to Reading, Writing, and Thinking in the Discipline - Cole, Stephanie; Breuer, Kimberly; Palmer, Scott W. (Open textbook library.)
Learn what it means to think like an historian! Units on “Thinking Historically,” “Reading Historically,” “Researching Historically,” and “Writing Historically” describe the essential skills of the discipline of history. “Performing Historically” offers advice on presenting research findings and describes some careers open to those with an academic training in history.